Psychological well-being during the pandemic - Исаханова, Асель (Pedagogy and Psychology, 2020)
Most of the research to date is based on the basic premise that the current situation of the coronavirus epidemic is stressful and has a negative impact on the psychological health, attitude and psychological well-being of people. In this regard, we decided to study the level of psychological well-being and life satisfaction during the pandemic, residents of the city of Nur-Sultan, aged 20 to 37 years. Due to the fact that psychological well-being is one of the main indicators of experiencing well-being, this study during the period of epidemiological threat becomes especially relevant in reflecting the psychological factors of psychological stability and stability of society as a whole. The study consisted of two stages, in which 600 people participated. The research methods were aimed at identifying the level of psychological well-being and life satisfaction during the first and second quarantines. the data obtained reflected the peculiarity of increasing indicators of psychological well-being during the second stage of quarantine.